Study Of Urinary Tract Infection in Pregnancy and Its Effect on Maternal and Perinatal Outcome - Dr. Tanzila Halim, Dr. Khairunnahar, Dr. Amena Khan, Dr. Umme Kulsum, Dr. Monowara Begum, Dr. Hasina Khatun (South Eastern European Journal of Public Health, 2025)
Background: Urinary tract infections (UTIs) are common during pregnancy and can lead to significant maternal and perinatal complications if not properly managed. Early detection and treatment are essential to preventing adverse outcomes such as preterm birth, low birth weight, and pyelonephritis. Aim of the study: The aim of this study was to investigate the prevalence of UTIs in pregnant women and their impact on maternal and perinatal outcomes. Methods: A cross-sectional study was conducted at the Department of Obstetrics & Gynecology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh over a period of January 2021 to December 2021 with 100 pregnant women diagnosed with UTIs. Clinical symptoms, urine analysis, and urine culture were used to identify UTI cases. Maternal complications, such as preterm labor and anemia, and perinatal outcomes, including preterm birth and low birth weight, were recorded. Statistical analysis was performed using SPSS software. Result: The majority of the women were aged 18-25 years (61.63%), with the second trimester being the most common period for UTI occurrence (60.47%). Escherichia coli was the most prevalent pathogen (66.28%). Maternal complications included preterm labor (22.09%) and anemia (25.58%), while perinatal outcomes showed preterm birth (26.74%) and low birth weight (33.72%). Conclusion: UTIs in pregnancy are associated with significant maternal and perinatal complications. The early diagnosis and treatment of UTIs, particularly during the second trimester, are crucial to prevent adverse outcomes. Routine screening and appropriate antimicrobial therapy are recommended to improve maternal and fetal health..